PERIOPERATIVE HEMODYNAMIC PARAMETERS IN OPTIMIZED HYPERTENSIVE PATIENTS POSTED FOR ELECTIVE SURGICAL PROCEDURES UNDER GENERAL ANAESTHESIA - Dr. Naveed Khan; Ozair Noor Trumboo; Dr. Abid Bashir Qadri (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Arterial hypertension is one of the most common co-morbid conditions affecting general population, which contributes to pathogenesis of various diseases, worsening the treatment outcome. Aim: To observe perioperative hemodynamic parameters in optimized hypertensive patients posted for elective surgical procedures under general anaesthesia. Methods: The present prospective observational study conducted in the Postgraduate Department of Anaesthesiology and Critical Care, Government Medical College, Srinagar and Associated Hospitals, over a period of 18 months on patients with optimized hypertension posted for elective surgical procedures under general anaesthesia. A total of 136 patients with controlled hypertension were observed and were classified according to duration of surgery. During the study period patients were observed for perioperative hemodynamic parameters in optimized hypertensive patients posted for elective surgical procedures under general anaesthesia, to observe the incidence of perioperative complications and any prolongation of hospital stay thereafter and to compare incidence of perioperative complications in surgeries of different durations. Results: Among 136 patients, 19.85% patients belonged to surgeries upto one hour of duration, 28.65% patients belonged to surgeries upto two hours of duration, 24.26% patients belonged to surgeries upto three hours of duration and 27.29% patients belonged to surgeries upto four hours of duration. All the patients demonstrated hemodynamic stability during anesthesia and showed no statistically significant deviation of hemodynamic parameters from pre-induction hemodynamic parameters during intraoperative and postoperative periods. Incidence of perioperative complications was 0% in surgeries of one hour duration, 2.5% in surgeries of 2 hours duration, 3.0% in surgeries of 3 hours duration and 5.4% in surgeries of 4 hours of duration. Conclusion: Controlled hypertension decreases the incidence of major perioperative complications such as arrhythmias, myocardial ischemia, and stroke.